2014
DOI: 10.1016/j.toxrep.2014.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic response to chronic bisphenol A exposure in C57bl/6n mice

Abstract: Fetal/neonatal exposure to the endocrine disruptor bisphenol A (BPA) has induced obesity and increased glucose intolerance. We hypothesized that chronic BPA exposure would worsen the obesity and glucose intolerance induced by a high fat diet (HFD). The drinking water of C57bl/6n dams was treated with vehicle (VEH) or BPA (25 ng/ml) from gestation day 11.5 to postnatal day 21. Another group was treated with oral diethylstilbestrol (DES, 1 μg/kg/day) during gestation. Progeny were treated with VEH (VEH and DES g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…On the other hand concentration of total cholesterol, both free and bound, has been increased in exposed groups of rats in our study. Similar findings have been reported, in case of BPA exposure [36] , [37] . BPS might increase the cholesterol concentration by inducing the peripheral cholesterol biosynthesis, increasing the degeneration of cell membranes in the process of cell apoptosis, and/or decreasing the level of HDL lipoprotein which carries cholesterol from dying cells to the liver for excretion.…”
Section: Discussionsupporting
confidence: 91%
“…On the other hand concentration of total cholesterol, both free and bound, has been increased in exposed groups of rats in our study. Similar findings have been reported, in case of BPA exposure [36] , [37] . BPS might increase the cholesterol concentration by inducing the peripheral cholesterol biosynthesis, increasing the degeneration of cell membranes in the process of cell apoptosis, and/or decreasing the level of HDL lipoprotein which carries cholesterol from dying cells to the liver for excretion.…”
Section: Discussionsupporting
confidence: 91%
“…Supporting the epidemiological results, early life exposure to BPA or the estrogenic compound diethylstilbestrol (DES) in mice and rats was correlated with increased body size and body weight in the adult progeny [26] , [38] , [51] , [60] . In contrast, chronic exposure to BPA did not lead to increased body size [30] , [42] .…”
Section: Introductionmentioning
confidence: 74%
“…In mouse models of myocardial infarctions several studies found chronic BPA exposure worsened outcomes 1416 . Furthermore, laboratory animal studies consistently show acute 5,17 and life-long 18,19 exposure of BPA at doses within the ranges seen in human populations has pro-arrhythmic effects. Studies showing negative cardiovascular effects of BPA exposure are particularly concerning given the widespread inclusion of BPA in medical devices which increase the levels in patients who are already at greater risk for cardiovascular complications 20 .…”
Section: Introductionmentioning
confidence: 92%